An Examination of Poverty as the Foundation of Crisis in Northern Nigeria. Issue 1 (January 2016) - Khan, Aslam; Cheri, Lawan
Northern Nigeria is a region that contradicts its natural endowments. Despite the existence of many economic resources such as tin, kaolin, a variety of agricultural products and a huge fertile land, the people remain in abject poverty leading to plethora of crisis in forms of insurgency, electoral violence and crime. Out of the six geopolitical zones in Nigeria, three are in the northern part of the country and they have the worst indices of poverty compared to the other zones. The Northwest with 77.7 per cent, North-central having 67.5 per cent and Northeast with 76.3 per cent, northern Nigeria becomes a hub of joblessness, crime, illiteracy, maternal mortality, early marriage and, recently, terrorism. This article uses content analysis to unravel the link between the present turmoil in northern Nigeria and the poverty indices that triggered the lingering crisis. This article shows that ineffectiveness of poverty alleviation programmes, poor resource utilisation, lack of private initiative and overdependence on scarce public jobs are the factors that caused and sustained poverty in northern Nigeria to serve as the foundation of the turbulence in all sectors of society. It recommends, inter alia, the strengthening of the private sector to provide jobs for the jobless, adherence to prudence, transparency and accountability in poverty alleviation programmes.